Role of Immune Checkpoint Inhibitor Therapy in Advanced EGFR-Mutant Non-Small Cell Lung Cancer - Wiest, Nathaniel; Majeed, Umair; Seegobin, Karan; Zhao, Yujie; Lou, Yanyan; Manochakian, Rami (Frontiers in Oncology, 2021)
Over the last decade, the treatment of advanced non-small cell lung cancer (NSCLC) has undergone rapid changes with innovations in oncogene-directed therapy and immune checkpoint inhibitors. In patients with NSCLC that harbors an epidermal growth factor receptor (EGFR) gene mutation (EGFRm), newer-generation tyrosine kinase inhibitors (TKIs) are providing unparalleled survival benefit and tolerability. Unfortunately, most of these patients will experience disease progression and thus an urgent need exists for improved subsequent lines of therapies. The concurrent revolution in immune checkpoint inhibitor (ICI) therapy is providing novel first and second line treatment options with improved clinical outcomes in wild-type EGFR (EGFRwt) NSCLC; however, the application of ICI therapy to advanced EGFRm NSCLC patients is controversial. Early studies demonstrated the inferiority of ICI monotherapy to EGFR TKI therapy in the first line setting and inferiority to chemotherapy in the second line setting. Additionally, combination ICI and EGFR TKI therapies have demonstrated increased toxicities, and EGFR TKI therapy given after first-line ICI therapy has been correlated with severe adverse events. Nonetheless, combination ICI therapies including dual-ICI blockade and ICI, chemotherapy, and angiogenesis inhibitors are areas of active study with some intriguing signals in preliminary studies. Here, we review previous and ongoing clinical studies of ICI therapy in advanced EGFRm NSCLC. We reviewed the data on ICI therapy in NSCLC with ALK, ROS1, BRAF, c-MET, RET, and NTRK mutations in a separate manuscript. We discuss advances in understanding the differences in the tumor biology and tumor microenvironment (TME) of EGFRm NSCLC tumors that may lead to novel approaches to enhance ICI efficacy. It is our goal to equip the reader with a knowledge of current therapies, past and current clinical trials, and exciting avenues of research that provide the promise of novel approaches and improved outcomes for patients with advanced EGFRm NSCLC.